Plasma Exosomal Proteomics Identifies Differentially Expressed Proteins as Biomarkers for Acute Myocardial Infarction - Jie Zhou; Hai-Tao Hou; Huan-Xin Chen; Yu Song; Xiao-Lin Zhou; Li-Li Zhang; Hong-Mei Xue; Qin Yang; Guo-Wei He (Biomolecules)
Myocardial infarction (MI), including ST-elevation MI (STEMI) and non-ST-elevation MI (NSTEMI), has been the leading cause of hospitalization and death. Exosomes participate in many physiological and pathological processes and have important effects on cell communication and function. This study analyzed the proteomic characteristics of plasma exosomes with the discovery of exosomal differentially expressed proteins (DEPs) in MI patients. Proteomics technology was used to identify the plasma exosomal DEPs in 41 patients in STEMI, NSTEMI, unstable angina, and CONTROL groups, and 406 exosomal DEPs were discovered. Further, 36 selected exosomal DEPs were validated with parallel reaction monitoring (PRM) in a new cohort of STEMI, NSTEMI, and CONTROL groups, and 7 were successfully verified. There were three (F13A1, TSPAN33, and YWHAZ) in the STEMI group and six (F13A1, TSPAN33, ITGA2B, GP9, GP5, and PPIA) in the NSTEMI group, and all were down-regulated compared to the CONTROL group with high sensitivity and specificity in MI that may be developed as biomarkers for MI and may become possible therapeutic targets for MI. Bioinformatics analysis revealed that these seven exosomal DEPs are of great significance in the molecular mechanism of MI. Therefore, the present study has provided insights to further explore the pathological mechanism and possible therapeutic targets in MI.